Cladding-Pumped Erbium/Ytterbium Co-Doped Fiber Amplifier for C-Band Operation in Optical Networks - Supe, Andis; Olonkins, Sergejs; Udalcovs, Aleksejs; Senkans, Ugis; Murnieks, Rihards; Gegere, Lilita; Prigunovs, Dmitrijs; Grube, Jurgis; Elsts, Edgars; Spolitis, Sandis; Ozolins, Oskars; Bobrovs, Vjaceslavs (MDPI, 2021)
Space-division multiplexing (SDM) attracts attention to cladding-pumped optical amplifiers, but they suffer from a low pump power conversion efficiency. To address this issue, ytterbium (Yb3+) and erbium (Er3+) co-doping is considered as an effective approach. However, it changes the gain profile of Er3+-doped fiber amplifiers and induces the gain difference between optical wavelengths in the C-band, significantly limiting the effective band of the dense wavelength-division multiplexed (DWDM) system. This paper is devoted to a detailed study of a cladding-pumped Er3+/Yb3+ co-doped fiber amplifier (EYDFA) through numerical simulations aiming to identify a configuration, before assembling a similar EYDFA in our laboratory premises that ensures the desired performance. The simulation model is based on a commercial double cladding EYDF whose parameters are experimentally extracted and fed to the EYDFA setup for the system-level studies. We investigate the wavelength dependence of the amplifier’s characteristics (absolute gain, gain uniformity, noise figure) and bit error rate (BER) performance for several DWDM channels and their optical power. The obtained results show that a 7 m long EYDF and co-propagating pump direction is preferable for the EYDFA with a 3 W pump source at 975 nm and with the given gain medium characteristics for WDM applications. For instance, it ensures a gain of 19.7–28.3 dB and a noise figure of 3.7–4.2 dB when amplifying 40 DWDM channels with the input power of −20 dBm per channel. Besides, we study EYDFA gain bandwidth and the maximum output power when operating close to the saturation regime and perform a sensitivity analysis showing how the doped fiber’s absorption and emission cross-sections impact the amplification process through energy transfer from Yb3+ to Er3+. Finally, we quantify the power penalty introduced by the EYDFA; the results show that it is not higher than 0.1 dB when amplifying 40 × 10 Gbps non-return-to-zero on-off keying signals from −20 dBm/channel.---//---This work is licensed under a CC BY 4.0 license.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; bit error rate; cladding-pumped optical amplifier; doped fiber amplifiers; erbium/ytterbium co-doping; optical fiber network; simulation; wavelength division multiplexing